An analysis of the value of token reinforcement using a multiple‐schedule assessment. Issue 1 (22nd July 2019) - Fiske, Kate E.; Isenhower, Robert W.; Bamond, Meredith J.; Lauderdale‐Littin, Stacy
Abstract : Token systems are widely used in clinical settings, necessitating the development of methods to evaluate the reinforcing value of these systems. In the current paper, we replicated the use of a multiple‐schedule reinforcer assessment (MSA; Smaby, MacDonald, Ahearn, & Dube, 2007) to evaluate the components of a token economy system for 4 learners with autism. Token systems had reinforcing value similar to primary reinforcers for 2 of the 4 learners, but resulted in lower rates of responding than primary reinforcers for the other 2 learners. Differentiated responding across learners may warrant variation in clinical recommendations on the use of tokens. The results of this study support formal assessment of token system effectiveness, and the MSA procedure provides an efficient method by which to conduct such assessments.